Selected work- related health problems among male agricultural workers in the Dambulla Medical Officer of Health (MOH) area. - Perera, G.S.N (My University, 2004)
This is a cross sectional descriptive study. A structered interviewer administered questionnaire and the rapid "field" test (Edson's modified method) to determine blood choline esterase levels were the two study instruments used. Only 395 (61.7 percent) farmers had engaged themselves in the spraying of pesticides within the previous three months. Of them 228 (57.7 percent) had experienced one or more symptoms of acurate pesticide poisoning. Commonly experienced symptoms were burning sensation of skin (17.5 percent), burning sensation of eyes (16.7 percent), headche (14.9 percent), difficulty in breathing (10.9 percent), nausea (10.4 percent) and vertigo (5.1 percent). The least known preventive measure was wearing of boots during spraying (32.5 percent). There was a significant association between knowledge on preventive measures with (a) educatinal status, (b) experience in agricultural work and (c) being involed in spraying. Knowledge on first aid measures following pesticide poisoning was significantly associated with educational status of the agricultural workers. Snake bite incidence among agricultural workers was 1,6 percent for one year period. Only 3 bites (30 percent) were venomous. The least known preventive measure was "treading the feet heavily when walking at night" (66.9 percent). There was a statistically significant association of occurrence of injuries with the educational status (p0.05). The least known first aid measure for bleeding wounds was "raising the affected body part above the level of the heart" (66.4 percent). In blood choline esterase level estimation, blood levels were reduced to 87.5 of the normal levels only among 9 (17 percent) farmers. All of them had engaged themselves in spraying during the previous one week. The time lapsed since exposure and the reduction of choline esterase levels had a statistically significant association. The knowledge and practices on preventive measures on pesticide spraying was not adequate. The practices that should be avoided following a snake bite were not known by a significant number of farmers. Recommend programmes to increase awareness and demonstrations to improve the skills on application of preventive and first aid measures. Recommend follow up studies with a compoment on observation of practices.